Modelling of vibration and noise control of a submerged circular plate - Wiciak, Jerzy (Archives of Acoustics, 2007)
This paper presents a numerical approach for modelling of a thin circular plate clamped onthe edges in a rectangular enclosure and containing distributed piezoelectric actuators underdynamic mechanical and electrical loadings. The plate is also loaded on one side by heavyfluid (water) and on the other side contacts with air. The finite element method analysis wasperformed, supported by the ANSYS computer package. The numerical solutions were confirmedexperimentally. The obtained results demonstrate a significant reduction of the vibrationlevel and sound pressure level with the use of piezoceramic actuators.